Sexual dimorphism and reproduction of the pitviper Porthidium ophryomegas (Serpentes: Viperidae) in Guatemala - Lawson, Dwight (Revista de Biología Tropical, 1996)
Porthidium ophryomegas is a slender, relatively small (to 770 mm) terrestrial pilviper inhabiting seasonally dry forests of lhe Pacific versant from south-central Guatemala to northwest Costa Rica with questionable records from eastern Panama (Campbell & Lamar 1989). This species also occurs in several rainshadow valleys of Ihe Atlantic drainage in Guatemala and Honduras.